Acute decompensated heart failure in patients with prediabetes: relationship with risk factors and comorbidities - N. A. Koziolova; S. V. Mironova; E. V. Ulybina (Российский кардиологический журнал)
Aim. To determine the incidence, risk factors and course of acute decompensated heart failure (ADHF) in patients with prediabetes.Material and methods. Within 24 months, 426 patients hospitalized to cardiology department of a multidisciplinary hospital with ADHF were consecutively included in the study. In addition, 136 patients who met the inclusion criteria and did not have exclusion criteria were divided into 2 groups depending on prediabetes presence. The first group consisted of 51 (37,5%) patients with prediabetes, the second — 85 (62,5%) patients without this pathology. ADHF was verified based on a rapid increase in symptoms and signs of hypoperfusion. Prediabetes was defined according to World Health Organization criteria. The risk level for type 2 diabetes was determined using the FINDRISC online calculator. In the first 48 hours of hospitalization, echocardiography was performed. The serum concentration of N-terminal pro-brain natriuretic peptide (NT-proBNP) and cystatin C was determined using enzyme immunoassay.Results. The incidence of prediabetes among patients with ADHF was 37,5%. In 9,8%, prediabetes was verified prior to hospitalization. Patients with prediabetes and ADHF were younger and were more likely to have obesity with a body mass index (BMI) of more than 30 kg/m2, non-alcoholic fatty liver disease, and higher waist circumference. In patients with ADHF and prediabetes, congestion symptoms were more pronounced, their higher frequency was recorded, as well as the frequency of wet-warm phenotype. Spironolactone dose was higher during hospitalization in the group of patients with ADHF and prediabetes. In the same group, the duration of hospitalization was longer. Prevalence of ADHF with preserved and mildly reduced ejection fraction (EF), severity of LV diastolic dysfunction (DD), LV mass index in patients with BMI >30 g/m2, left atrial volume index, pulmonary artery systolic pressure were significantly higher in the group of patients with ADHF and prediabetes. At a high risk of type 2 diabetes, the concentrations of NT-proBNP, triglyceride/glucose index, cystatin C, LV diastolic dysfunction severity were significantly higher, and the glomerular filtration rate was lower.Conclusion. The development of ADHF in patients with prediabetes is interrelated with multiple risk factors and comorbidities, characterized by more pronounced congestion, longer hospitalization, predominantly preserved and mildly reduced EF in combination with severe LVDD, LV hypertrophy, and activation of nonspecific inflammation.